PERAN BUZZER MEDIA SOSIAL INSTAGRAM DALAM MEMBENTUK BRAND PRODUK SUSU ALLESGUT (Lembaga Pengembangan Kinerja Dosen, 2024)
Social media in the last decade has become a channel that greatly influences all sectors of public life. It allows companies to see what topics are being discussed, what customers want in certain products on social media. The rapid dissemination of product information makes it easy for a brand to be known by Instagram social media users. On Instagram, there are many ways to promote products such as the Instagram Buzzer. The message delivered by buzzers on Instagram is done by combining captions with photos that are interesting and appropriate to the product being promoted. The buzzer's language style is also adapted to each character and is not given specific guidelines or formats. The research entitled